Standard wound management versus negative-pressure wound therapy in the treatment of adult patients having surgical incisions for major trauma to the lower limb—a two-arm parallel group superiority randomised controlled trial: protocol for Wound Healing in Surgery for Trauma (WHIST). Issue 6 (7th June 2018) - Achten, Juul; Vadher, Karan; Bruce, Julie; Nanchahal, Jagdeep; Spoors, Louise; Masters, James P; Dutton, Susan; Madan, Jason; Costa, Matthew L
Abstract : Introduction: Patients with closed high-energy injuries associated with major trauma have surprisingly high rates of surgical site infection in incisions created during fracture fixation. One factor that may reduce the risk of surgical site infection is the type of dressing applied over the closed surgical incision. In this multicentre randomised clinical trial, negative-pressure wound therapy will be compared with standard dressings with outcomes of deep infection, quality of life, pain and disability. Methods and analysis: Adult patients presenting to hospital within 72 hours of sustaining major trauma, requiring a surgical incision to treat a fractured lower limb, are eligible for inclusion. Randomisation, stratified by trial centre, open/closed fracture at presentation and Injury Severity Score (ISS) ≤15 versus ISS ≥16 will be administered via a secure web-based service using minimisation. The random allocation will be to either standard wound management or negative-pressure wound therapy. Trial participants will usually have clinical follow-up at the local fracture clinic for a minimum of 6 months, as per standard National Health Service practice. Diagnosis of deep infection will be recorded at 30 days. Functional, pain and quality of life outcome data will be collected using the Disability Rating Index, Douleur Neuropathique Questionnaire and Euroqol - 5 Dimension - 5 level (EQ-5D-5L) questionnaires at 3 months and 6 months postinjury. Further data will be captured on resource use and any late postoperative complications. Longer term outcomes will be assessed annually for 5 years and reported separately. Ethics and dissemination: National Research Ethics Committee approved this study on 16 February 2016 16/WM/0006. The National Institute for Health Research Health Technology Assessment monograph and a manuscript to a peer-reviewed journal will be submitted on completion of this trial. The results of this trial will inform clinical practice on the clinical and cost-effectiveness of the treatment of this injury. Trial registration number: ISRCTN12702354 ; Pre-results.